Targeting apoptosis pathways in cancer therapy - Fulda, Simone (Henry Stewart Talks, 2007)
Apoptosis in cancer, Apoptosis signalling pathways, Death receptor pathway, Mitochondrial pathway, Targeting the death receptor pathway, Bcl-2 family proteins: structure and function, Targeting Bcl-2 family proteins, IAPs: structure and function, Targeting IAPs
Reviewed at 2019/11/22